Experimental verification of numerical model of integral bridge - Jarosz, Jakub (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the results of analyses of displacements for a real reinforced concrete integral bridge. The research consisted of the measurement of vertical displacement in the middle of the span and lateral displacement of the abutment. Ten load cases were considered. Two of them concerned vehicles placed motionlessly, the rest ones – braking vehicles. Moreover, the influence of initial braking velocity was analysed. The results of research were compared with numerical simulations. Two options of numerical models were considered. In the first case, cooperation between construction of span and road layers was ignored, but in the second one it was not. In the both options, the same soil conditions were assumed.Cooperation between construction and road layers was took into consideration by the increase of stiffness of span. A real heterogeneous cross section was reduced to homogeneous one. Road layers were converted to equivalent concrete layers. Neutral axis, moment of inertia and thickness were calculated for a reduced cross section and applied into model.Relations between displacements and duration were presented for load cases with braking vehicles. Displacements due to braking forces and static load were compared.